Peran Kopontren dalam Meningkatkan Kompetensi Wirausaha Santri - Hakim, Muhammad Arif; Lailiyyah, Hurrotul; Widayanti, Yuyun (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2023)
This study aims to identify the progress of cooperatives located in At-Taslim Islamic Boarding School, Bintoro Village, Demak District, Demak Regency. Entrepreneurial activities carried out within the framework of Kopontren, as well as the role of Kopontren At-Taslim in improving the entrepreneurial skills of students are interesting findings. This research was conducted using field research methods and using a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving informants related to the research issue. The results of this study noted that entrepreneurial activities carried out in the At-Taslim Kopontren environment include the At-Taslim Kopontren business unit in Bintoro Village, the